UR_GERICHTE 2018_OG BI 18 5 vom 3. Mai 2018 , 2018_OG BI 18 5. Strafprozessordnung. Art. 382 Abs. 1, Art. 431 Abs. 1 und Art. 319 StPO. - UR Obergericht (2018)
Strafprozessordnung. Art. 382 Abs. 1, Art. 431 Abs. 1 und Art. 319 StPO.